TAXONOMIC DESCRIPTION AND ANTIBACTERIAL ACTIVITY OF DILLENIA sp. AGAINST ESCHERICHIA coli - Shiena Mae Martina; Gene Patrish Cabalquinto; Leonel Lumogdang (SEAMEO BIOTROP, 2024)
Article Highlights- The study first reported taxonomic study of Dillenia sp. in Malita, Davao, Occidental Philippines. - This is the first reported findings of the bacterial activity of the bark extract of Dillenia sp. against Escherichia coli. AbstractThe study aimed to provide a taxonomic description of Dillenia sp. and evaluate its antibacterial activity against Escherichia coli (E. coli). The taxonomic description was characterized using the taxonomic keys and field guides. The antibacterial activity of Dillenia sp. was screened using the Kirby-Bauer disk diffusion assay. Taxonomic description confirms Dillenia sp. to be an angiosperm flowering seed plant native to the Philippines, characterized by its round-shaped growth and evergreen foliage. The antibacterial activity of Dillenia sp. bark extracts against E. coli were assessed using different concentrations (100 ppm, 500 ppm, and 1000 ppm) and extraction solvents (ethanolic, aqueous, and decoction). There are significant differences in the antibacterial activity observed among treatments within the decoction extracts, indicating varying effects on antibacterial activity. Post-hoc analysis revealed that concentrations of 100 ppm and 500 ppm were significantly more effective in inhibiting bacterial growth compared to 1000 ppm within the Decoction treatment. Each treatment showed distinct patterns of antibacterial activity, with ethanolic and aqueous extracts displaying relatively consistent activity across different concentrations, while the decoction extract exhibited concentration-dependent antibacterial activity. The study provides evidence of the antibacterial potential of Dillenia sp. bark extracts against Escherichia coli, with implications for further research and potential practical applications in combating bacterial infections. Recommendations include exploring different lower concentration ranges, considering different treatment formulations, investigating combination treatments, and assessing antimicrobial mechanisms to enhance efficacy and guide the development of novel antibacterial strategies.